PROCEDURES FOR RECEIVING ZAKAT,INFAQ,SHODAQOH AND WAQF FUNDS AT THE SIDOARJO INDEPENDENT ORPHANAGE FOUNDATION - Intan Parawansa; Musdin La Nurdin; Achmad Sjamsudin (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
The Yatim Mandiri Foundation is a National Amil Zakat Institution (LAZNAS) owned by the Indonesian people who is solemn to raise the social dignity of humanity for orphans with ZISWAF funds (Zakat, Infaq, Shodaqoh, Waqf) as well as other halal and legal funds, from individuals, groups, and companies. /institution. This research uses descriptive qualitative analysis research. Where qualitative is an analysis that is not based on statistical calculations in the form of quantitative (amount), but in the form of statements and descriptions which will then be compiled in the form of reports. The procedure for receiving ZISWAF funds at the Yatim Mandiri Foundation is allocated in several foundation programs, namely the Charity Program, Enpowerment Program, and Education Program. To attract customers/consumers, the agency's ZIS consultants are guided not only to provide product services but also to provide comfort and information to consumers. Signals to consumers can be given through small talk with consumers or praying together with consumers. The distribution of donations is done by channeling these funds to implement programs at Laznas Yatim Mandiri Foundation, Sidoarjo Branch. With these funds, programs at Laznas Yatim Mandiri Foundation Sidoarjo Branch can be carried out every month. Keywords: zakat, infaq, shodaqoh, waqf, management References Majalah Lembaga Amil Zakat Nasional Yayasan Yatim Mandiri. 2021. Surabaya Brosur Lembaga Amil Zakat Nasional Yayasan Yatim Mandiri. 2021. Surabaya Berita diakses dari www.yatimmandiri.org. Pada tanggal 29 November 2021 Diakses dari http://digilib.uinsby.ac.id/2139/5/Bab3 . Pada tanggal 29 November 2021